Distributed cognition in classical antiquity - Anderson, Miranda; Cairns, Douglas; Sprevak, Mark, 1977- (Edinburgh history of distributed cognition., 2019)
This collection explores how cognition is explicitly or implicitly conceived of as distributed across brain, body and world in Greek and Roman technology, science, medicine, material culture, philosophy and literary studies. A range of models emerge, which vary both in terms of whether cognition is just embodied or involves tools or objects in the world. As many of the texts and practices discussed have influenced Western European society and culture, this collection reveals the historical foundations of our theoretical and practical attempts to comprehend the distributed nature of human cognition. Key Features: The first book in an ambitious four-volume set looking at distributed cognition in the history of thought. Includes essays on archaeology, art history, rhetoric, literature, philosophy, science, medicine and technology.